Effect of Smoking during pregnancy on the Dimension of the Newborn and Anthropometric Indices: a cohort study in Lattakia, Syria - Maarouf, Abeer Adeeb; Mohammad, Basel; Alnukkari, Mohammad (Journal of medical and pharmaceutical sciences, 2022)
Objective: To investigate the effect of smoking during pregnancy on the anthropometric measurements of the newborn and the effect of stopping smoking during the first trimester of pregnancy. Patients and methods: Our study was a cohort-analytical study conducted at Tishreen University Hospital in Lattakia-Syria during the period from January 2020 to January 2021. The study included 180 pregnant women with a single live pregnancy who met the inclusion criteria. They were divided into non-smokers, smokers who stopped smoking during the first trimester of pregnancy (group 1), smokers who continued smoking until the end of pregnancy (group 2). After birth. Neonate identified with Small for gestational age and low birth weight. Results: The study was founded that smoking during pregnancy increases the risk of (low birth weight) LBW by 16.3% and the risk of SGA (small for gestational age) by 79%, and smoking was associated with the birth of children with lower anthropometric measurements compared to the children of non-smoking mothers. As for the Ponderal Index >90th, A.OR was 4.9 for group (1) versus 5.8 for group (2) and Head to Length Ratio >90th was 3.4 for group (1) versus 4.6 for group (2), as it was found that increasing the number of cigarettes smoked per day increases the risk of The occurrence of adverse birth outcomes Conclusion: Maternal smoking, regardless of duration of smoking during pregnancy, was associated with neonates abnormal body proportions resulting from greater reductions in body length and head circumference compared to weight, smoking during the first trimester of pregnancy was associated with adverse birth outcomes, but with a lower A.OR than group (2).